Educational inequality and digital divide: a post-technological acceleration analysis (Revista Investigación & praxis en CS Sociales, 2025)
The COVID-19 pandemic acted as an unforeseen catalyst for technological adoption in education globally. While this acceleration opened new avenues for learning, it also exacerbated pre-existing educational inequalities, closely linked to the digital divide. This bibliographic study analyzed academic literature and relevant reports published mainly between 2020 and 2024 to investigate the reconfiguration of educational inequality in the context of increased reliance on digital technologies. The dimensions of the digital divide (access, use, and skills) and their differential impact on various student groups were examined. The research delved into how policies implemented during and after the health crisis addressed, or failed to address, these disparities. Findings indicated that, despite efforts, the rapid transition to remote education and hybrid models tended to widen differences in learning outcomes, disproportionately affecting students from vulnerable socioeconomic backgrounds, rural areas, and those with special educational needs. It was concluded that the mere provision of technology was insufficient without comprehensive strategies addressing digital competencies, adequate pedagogical support, and underlying socioeconomic barriers. This analysis underscored the urgency of inclusive and equitable educational policies in the digital age.
Keywords: educational inequality; digital divide; COVID-19; technological acceleration; digital inclusion, educational policy